Data ingestion into NeQuick 2 - Nava, Bruno (2011)
NeQuick 2 is the latest version of the NeQuick ionosphere electron density model developed at the Aeronomy and Radiopropagation Laboratory of the Abdus Salam International Centre for Theoretical Physics (ICTP) - Trieste, Italy with the collaboration of the Institute for Geophysics, Astrophysics and Meteorology of the University of Graz, Austria. It is a quick-run model particularly designed for trans-ionospheric propagation applications that has been conceived to reproduce the median behavior of the ionosphere. To provide 3-D specification of the ionosphere electron density for current conditions, different ionosphere electron density retrieval techniques based on the NeQuick adaptation to GPS-derived Total Electron Content (TEC) data and ionosonde measured peak parameters values have been developed. In the present paper the technique based on the ingestion of global vertical TEC map into NeQuick 2 will be validated and an assessment of the capability of the model to reproduce the ionosphere day-to-day variability will also be performed. For this purpose hourly GPS-derived global vertical TEC maps and hourly foF2 values from about 20 ionosondes corresponding to one month in high solar activity and one month in low solar activity period will be used. Furthermore, the first results concerning the ingestion of space-based GPS-derived TEC data will be presented.